2011
DOI: 10.1001/archoto.2011.61
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Human Adipose Tissue–Derived Stromal Cells Induce Mandibular Bone Healing in Rats

Abstract: Undifferentiated human ATSCs are suitable for cell-based treatment of mandibular defects, even in the absence of previous osteogenic induction in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Cell-based approaches are mainly based on mesenchymal stem cells (MSCs), that have been widely employed, in conjunction with appropriate osteoinductive scaffolds, and considered the most effective bioactive bone substitutes “in vivo” [172, 176, 177]. …”
Section: Emerging Strategies For Bone Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-based approaches are mainly based on mesenchymal stem cells (MSCs), that have been widely employed, in conjunction with appropriate osteoinductive scaffolds, and considered the most effective bioactive bone substitutes “in vivo” [172, 176, 177]. …”
Section: Emerging Strategies For Bone Substitutionmentioning
confidence: 99%
“…It is noteworthy that naïve undifferentiated MSCs are prone to environment-induced lineage commitment [186] meaning that they can undergo spontaneous osteogenic differentiation upon “in vivo ” inoculation into a damaged bone [187, 176]. This feature may suggest their safe use as it does not imply any kind of “ex vivo ” osteogenic induction prior to “in vivo ” inoculation.…”
Section: Emerging Strategies For Bone Substitutionmentioning
confidence: 99%
“…Interestingly, ASCs proved to allow bone regeneration in vivo , without the need for ex vivo engineering and/or induction [12]. Also, it has been clearly demonstrated that allogeneic ASCs displays a nonimmunogenic profile in vitro and does not evoke cell-based immunity when implanted in a rat spinal fusion model [66].…”
Section: Cell-therapies For Spinal Fusionmentioning
confidence: 99%
“…The improved knowledge on adult stem cell biology and of mesenchymal stem cell features allowed their use in regenerative medicine, with particular focus on bone regeneration. In particular, cell-based approaches based on mesenchymal stem cells (MSC) have been widely employed and considered the most effective for bone formation and regeneration in vivo [12, 13]. In addition, the overwhelming amount of studies that have been investigating the molecular scenario orchestrating osteogenesis and bone healing, provided new osteoinductive molecules to be tested as potential drugs in spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that the ready availability of these cells following orthopaedic injuries (involving traumatised muscle tissue) makes them an attractive possible cell source for regenerative medicine approaches. Adipose tissues also provide a readily available source of stromal cells, and adipose derived stromal cells have been used to successfully regenerate bone (Parrilla et al 2011;Levi et al 2010).…”
Section: Auto-transplantation and Homing Of Endogenous Cellsmentioning
confidence: 99%